Online English Shadow Education: EFL Learners’ Perspective - Fatin Nadifa Tarigan; Elgie Septiya Lasnumanda (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
A number of shadow education (private supplementary tutoring) of English have emerged in Indonesia regarding the fulfillment of students’ variety of needs in learning English that is not fully accommodated in mainstream schooling. Apparently, the services provided in shadow education have been transferred in online setting due to the rapid advancement of technology. This research aims at observing the EFL learners’ perspective on online English shadow education. With descriptive qualitative design, the subjects were involving 28 EFL learners experiencing English shadow education in KII online English course. The data were collected from the questionnaire developed in closed- and open-ended format. This research reports the result of a survey research on EFL learners’ perspective on online English shadow education that EFL learners’ participation were not only led by the same reasons of the conventional one but the practicality also contributes on it and challenges faced by the learners were revealed as well. Technical issues such as bad internet connection and limited interaction between the tutor and the learner were the major case in online English shadow education. Moreover, EFL learners also admitted that they suffer from self-regulation learning strategy and it relates to teaching pedagogy as well. These results have implications for EFL practitioners aiming at better understanding current EFL learners.